EKSISTENSI BPKP DALAM PENGAWASAN KEUANGAN DAN PEMBANGUNAN - SUSENO, AGUNG (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The existence of BPKP financial and development control is still in dilemma, because in the process of controlling it still encounters problems. This research aimed to describe the controlling process, the controlling problem, and the performance of BPKP (Board of Finance and Development Control). This research used qualitative approach with the method of in-depth interview. The result of this research indicated that BPKP still encountered problems such as human resource quality, budgets, facilities, working method, negative perception from society, and dominant external controller. Despite all the problems, BPKP still plays an important role in controlling Indonesian finance and development.